The mediaeval mystics of England - Colledge, Edmund, 1910-1999; O'Brien, Elmer J. (London : Murray, 1962)
Een bundeling van de Middeleeuws Engelse mystieke werken van St. Aelred of Rievaulx, St. Edmund Rich, Richard Dolle, Walter Hilton, Julian of Norwich, ...
St. Aelred of Rievaulx : The mirror of love, excerpts from Book 1 -- St. Edmund Rich : The mirror of holy church -- Richard Rolle : I sleep and my heart wakes -- The author of The cloud of unknowing : The book of privy counsel -- Walter Hilton : The scale of perfection, excerpts from Books 1 and II -- Julian of Norwich : Revelations, chapter 50 and 51 -- Excerpt from The book of Margery Kempe.
Originally published: New York : Scribner, ©1961.
Includes bibliographical references (pages 90-102).
Keywords: 600-1500.; Mysticism -- History -- Middle Ages, 600-1500.; Mysticism -- Middle Ages; Mysticism -- Great Britain; Mysticism; Great Britain; History